2009
DOI: 10.1089/ars.2009.2430
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of LRRK2 and α-Synuclein in Parkinson's Disease

Abstract: Current treatments for Parkinson's disease fail to modify disease progression and the underlying pathegenic mechanisms remain elusive. The identification of specific targets responsible for disease will aid in the development of relevant model systems and the discovery of neuroprotective and neurorestorative therapies. Two promising protein candidates, alpha-synuclein and LRRK2, offer unique insight into the molecular basis of disease and the potential to intervene in pathogenesis. Although multiple lines of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 279 publications
(333 reference statements)
1
12
0
2
Order By: Relevance
“…Consistent with these studies a-synuclein-null mice showed heightened resistance to MPTP and other mitochondrial toxins (17). As indicated above, use of drugs that upregulate chaperones such as Hsp70 to block a-synuclein aggregation has shown efficacy in both in vitro and in vivo models of disease (14,16). Other means to block a-synuclein aggregation includes use of synthetic peptides derived from the N-terminal amino acid sequence of a-synuclein, and human single-chain antibody fragments (scFv) that binds a-synuclein to inhibit formation of toxic a-synuclein fibrils.…”
Section: Infiltration Of T Cells Has Been Found In Brains Of Pd Patiesupporting
confidence: 66%
See 3 more Smart Citations
“…Consistent with these studies a-synuclein-null mice showed heightened resistance to MPTP and other mitochondrial toxins (17). As indicated above, use of drugs that upregulate chaperones such as Hsp70 to block a-synuclein aggregation has shown efficacy in both in vitro and in vivo models of disease (14,16). Other means to block a-synuclein aggregation includes use of synthetic peptides derived from the N-terminal amino acid sequence of a-synuclein, and human single-chain antibody fragments (scFv) that binds a-synuclein to inhibit formation of toxic a-synuclein fibrils.…”
Section: Infiltration Of T Cells Has Been Found In Brains Of Pd Patiesupporting
confidence: 66%
“…Interestingly flies expressing wild-type dLRRK or dLRRK2 with mutations predicted to inactivate kinase activity failed to develop dopaminergic toxicity. This in vivo study suggests that the LRRK2 kinase activity could serve as a valid target for neuroprotection for PD, although additional studies will be required from multiple in vivo models to definitively prove that LRRK2 kinase activity is indeed an ideal target for drug development (14).…”
Section: Thomasmentioning
confidence: 89%
See 2 more Smart Citations
“…Pathological mutations in the LRRK2 protein often cause phenotypes similar to the more prevalent idiopathic late-onset PD, suggesting a shared etiology between the two diseases 39 . The most straightforward approach to hone in on the pathogenic activity associated with LRRK2 may lie in successful identification of the difference between mutant and WT protein.…”
Section: Discussionmentioning
confidence: 99%